1997
DOI: 10.1061/(asce)0733-9437(1997)123:6(423)
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Performance Measures: Efficiency and Uniformity

Abstract: It is essential to standardize the definitions and approaches to quantifying various irrigation per formance measures. The ASCE Task Committee on Defining Irrigation Efficiency and Uniformity provides a comprehensive examination of various performance indices such as irrigation efficiency, application efficiency, irrigation sagacity, distribution uniformity, and others. Consistency is provided among different irrigation meth ods and different scales. Clarification of common points of confusion is provided, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
293
0
27

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 502 publications
(338 citation statements)
references
References 7 publications
1
293
0
27
Order By: Relevance
“…It is clear that increasing irrigation efficiency does not necessarily make more water available for other uses. Water availability for other uses can only be increased by decreasing consumption (Burt et al, 1997). The decision to whether enhancing efficiency is an instrument for water conservation or alternatively a mean to promote agricultural production and income is a policy question that needs to be considered and solved in a transparent way in the public arena.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that increasing irrigation efficiency does not necessarily make more water available for other uses. Water availability for other uses can only be increased by decreasing consumption (Burt et al, 1997). The decision to whether enhancing efficiency is an instrument for water conservation or alternatively a mean to promote agricultural production and income is a policy question that needs to be considered and solved in a transparent way in the public arena.…”
Section: Discussionmentioning
confidence: 99%
“…On a basin or global scale, conservation should have the objective of reducing the consumptive component [Allen et al, 1996[Allen et al, , 1997Burt et al, 1997]. However, consumption is rarely the focus of conservation programs.…”
Section: Water Balance and Water Conservationmentioning
confidence: 99%
“…[28] Burt et al [1997] suggested a systematic way to categorize the water that is diverted for irrigation. In evaluating the performance of irrigation systems, one has to be careful to establish appropriate physical boundaries and time frames, since water is often in transit or in temporary storage.…”
Section: Water Balance and Water Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydraulic water use efficiency was computed by dividing the net crop water requirement (NCWR) to the total water applied (TWA) (Burt et al, 1997). HWUE = NCWR/ TWA ……..…... (11) Adam et al, 043…”
Section: Hydraulic Water Use Efficiency (Hwue)mentioning
confidence: 99%